2000
DOI: 10.12968/bjtr.2000.7.8.13862
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the power balance in physiotherapy

Abstract: All social interactions involve an element of power negotiation. In the physiotherapeutic situation, there are a number of interesting opportunities to exercise power to a greater extent than would be possible in normal day-to-day life. The power balance of the clinical encounter is explored from both the patient’s and the physiotherapist's perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In addition, in another study, 42 patients commented that the physiotherapist was 'rushed' which might be interpreted by patients as a lack of interest in them. 58 Patient-satisfaction has been previously related to accessibility, availability and convenience. 59…”
Section: Description Of Resultsmentioning
confidence: 99%
“…In addition, in another study, 42 patients commented that the physiotherapist was 'rushed' which might be interpreted by patients as a lack of interest in them. 58 Patient-satisfaction has been previously related to accessibility, availability and convenience. 59…”
Section: Description Of Resultsmentioning
confidence: 99%
“…The names of the participants were anonymized using a numerical code assigned for the transcripts and quotations. A modified constant comparison methodology was used for data analysis [44,45]. Three authors (JMB, ORN, MCMG) independently reviewed the transcripts and coded sentences containing significant units of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Harrison et al [44], conducted a study with patients and physical therapists and found that patients were dissatisfied when they noticed that their physical therapists seemed rushed, which they interpreted as a lack of interest in the patient. In turn, the physical therapists regretted not having enough time to "treat patients to their satisfaction".…”
Section: Discussionmentioning
confidence: 99%
“…When viewed in the context of previous findings, it seems plausible that, without explicit communication, patients may feel subjugated in a way that undermines the clinicians’ attempts to practice patient-centered care. For example, Harrison and Williams (2000) reported that, where physiotherapists felt the power imbalance between themselves and their patients was not significant, the patients found it overwhelming to the extent that their experiences did not reflect the collaborative patient-centered care model promoted by government policy. Financial and organizational factors, as reported here, can also cause dilemmas in patient–clinician interactions and a deprioritization of patient-centered goals (Levack et al, 2011).…”
Section: Discussionmentioning
confidence: 99%